MORPHOLOGICAL SUFFIXES IN THE ARTICLE OF THE JAKARTA POST ONLINE NEWSPAPER - Dina Nurtiddini; Laila Soraya (PROJECT (Professional Journal of English Education), 2019)
This study was designed in the form of descriptive qualitative research with the aim at describing the most frequently used suffix in the article entitled “British Company to Invest $200m in West Java waste-to-fuel Plants” from online newspaper The Jakarta Post that published on 4th of March 2019. Documentation is the techniques of data collecting used in this study by reading, analyzing the text, gathering, and counting the suffixes used. The result showed that there are 83 data of suffixes found with 62 data are inflectional suffixes consist of 37% suffix –s (31 data), 18% suffix –ed (15 data), 18% suffix –ing (15 data), and 1% suffix –er (1 data). The rest of 21 data found are derivational suffixes, consist of 1% suffix –able, –ant, –ate, –ation,  –ition, –in, –or, –ship, and –ty with each suffix consist of 1 data. The other forms of derivational suffixes found are 5% suffix –ion (4 data), 5% suffix –ly (4 data), 3% suffix –ment (2 data), and 3% suffix –y (2 data). Thus, the writers concluded that inflectional suffixes with the form of suffix –s is the most frequently used suffix in the article.